The Effects of NLR on the Diagnosis and Pharmacological Management of Brain Abscesses - Ibrahim Yilmaz; Tezcan Çalışkan; Emel Ersoz; Mustafa Doğan; Numan Karaarslan; Fatma Hacıoglu (Acta Medica Alanya)
Aim: The present study aims to examine the effectiveness of the neutrophil-to-lymphocyte ratio in the treatment and diagnosis of patients with brain abscesses.Method: In this retrospective study, radiological, neurological, and surgical data obtained from the medical records of healthy volunteers (n = 10) who presented to the hospital for check-ups and patients with brain abscesses who were treated (n = 10) were evaluated statistically. Alpha significance value was accepted as <0.05.Results: Comparisons between groups revealed that the erythrocyte sedimentation rate, C-reactive protein, leukocyte, and neutrophil values were statistically significant (P <0.05) while lymphocyte value was not statistically significant (P >0.05). The preoperative neutrophil-to-lymphocyte ratio in cases diagnosed with brain abscesses showed statistical significance compared to that in the healthy volunteers (P <0.05) and the neutrophil-to-lymphocyte ratio increased 3.31-fold in the study group compared to the healthy volunteers.Conclusion: A strong positive strong relationship between the neutrophil-to-lymphocyte ratio and abscess size (r = 0.662; P = 0.037) was observed. An increased neutrophil-to-lymphocyte ratio may serve as an early warning signal of brain abscesses.Keywords: Antibiotic treatment; brain abscess; low-cost diagnosis method; magnetic resonance image; neutrophil-to-lymphocyte ratio.